Approaches and Tools to Study the Roles of Juvenile Hormones in Controlling Insect Biology - Noriega, Fernando G; Nouzova, Marcela (Insects, 2020)
The juvenile hormones (JHs) are a group of sesquiterpenoids synthesized by the corpora allata. They play critical roles during insect development and reproduction. To study processes that are controlled by JH, researchers need methods to identify and quantify endogenous JHs and tools that can be used to increase or decrease JH titers in vitro and in vivo. The lipophilic nature of JHs, coupled with the low endogenous titers, make handling and quantification challenging. JH titers in insects can easily be increased by the topical application of JH analogs, such as methoprene. On the other hand, experimentally reducing JH titers has been more difficult. New approaches to modulate JH homeostasis have been established based on advances in RNA interference and CRISPR/Cas9-based genome editing. This review will summarize current advances in: (1) the detection and quantification of JHs from insect samples; (2) approaches to manipulating JH titers; and (3) next-generation tools to modulate JH homeostasis.
Keywords: JH titer; juvenile hormone; JH signaling